1982
DOI: 10.1111/j.1095-8649.1982.tb03956.x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of salmonids in upland streams in relation to depth and gradient

Abstract: The distribution of various age classes of salmon and trout was assessed in upland streams by electrofishing. Water depths and site gradients were measured and correlated to fish densities. The fry of both species were significantly more abundant in shallow water; up to 75.3% of salmon fry and 72.2% of trout fry were captured in sites of mean depth < 20 cm.Older trout were found mainly in the deeper areas, with a maximum of 7.4% captured in sites < 20 cm mean depth. Yearling fish were found in all the depth-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 14 publications
8
86
1
1
Order By: Relevance
“…Previous studies have illustrated the key importance of water depth in determining juvenile brown trout habitat use (Bohlin, 1977;Bagliniere and Champigneulle, 1982;Egglishaw and Shackley, 1982;Kennedy and Strange, 1982;Heggenes, 1988c, d), including Danish small lowland streams (Hermansen and Krog, 1984). All of the above studies and others have shown that there is a positive correlation between fish size and water depth, and that the larger the trout, the deeper water it prefers (Greenberg et al, 1996;Heggenes et al, 1999;Maki-Petays et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have illustrated the key importance of water depth in determining juvenile brown trout habitat use (Bohlin, 1977;Bagliniere and Champigneulle, 1982;Egglishaw and Shackley, 1982;Kennedy and Strange, 1982;Heggenes, 1988c, d), including Danish small lowland streams (Hermansen and Krog, 1984). All of the above studies and others have shown that there is a positive correlation between fish size and water depth, and that the larger the trout, the deeper water it prefers (Greenberg et al, 1996;Heggenes et al, 1999;Maki-Petays et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…There is little knowledge on physical habitat requirements in small lowland streams that can be used to evaluate the effects of different water management actions such as water abstraction or stream restoration activities aimed at increasing stream flow and improving physical habitat conditions Conallin et al, 2010a;Nislow and Armstrong, 2012). Four habitat variables are known to affect the habitat selection of salmonids and carrying capacity in streams (Vezza et al, 2012); water depth (Kennedy and Strange, 1982;Heggenes, 1988aHeggenes, , 2002, water velocity (Heggenes and Traaen, 1988;Heggenes et al, 1999;Heggenes and Dokk, 2001), bed substrate (Heggenes, 1988b;Knapp and Preisler, 1999;Kondolf, 2000), and cover (Hubert et al, 1994;Bovee et al, 1998). However, differences in stream characteristics can influence the importance of these variables on brown trout habitat selection, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that habitat needs may alter with the life-stage, size and species concerned (MILNER et al, 1981 ;KENNEDY and STRANGE, 1982 ;MORANTZ et al, 1987). It is likely, therefore, that the dérivation of successfui models may, in part, be a resuit of their specificity.…”
Section: Generalmentioning
confidence: 99%
“…Within a stream at any one time, local features are demonstrably important (e.g. LEWIS, 1969 ;GORDON and MACCRIMMON, 1982 ;KENNEDY and STRANGE, 1982), but over time they may explain only small proportions of overall variance, particularly if random factors keep the population below levels where habitat is limiting. Thus, caution should be applied to model performance expressed in this way which disregards the temporal variability, some of which will be synchronous and some of which will be contained as site-year interaction within the error variance.…”
Section: Vmentioning
confidence: 99%